2020
DOI: 10.18203/2320-6012.ijrms20201327
|View full text |Cite
|
Sign up to set email alerts
|

Audit of fresh frozen plasma usage, prospective study: a report from department of immunohematology and transfusion medicine, government medical college Jammu, Jammu and Kashmir, India

Abstract: Background: Fresh frozen plasma is commonly used in tertiary care hospitals. These are used to manage conditions such as coagulation derangements. Unnecessary use of fresh frozen plasma (FFP) is known to increase the risk of side effects in plasma transfusing patients like anaphylaxis, transfusion related acute lung injury (TRALI) and risk of transfusion transmitted infections etc. So judicious use of plasma is extremely important where its benefits outweigh its potential risks.Methods: Prospective observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Whereas appropriateness of FFP usage was 67 & 66.44% in recent studies conducted by Puri V et al & shah N et al respectively which is similar with our study. 26,23 Comparative analysis of FFP audits show varied indications of inappropriate use including volume expansion, bleeding with normal coagulation profile, or non-available coagulation profile leading cause of inappropriate use in our study was found to be in bleeding or non-bleeding patients with PT/INR non availability or within normal limits or mildly elevated. Luk et al found maximum patients to be inappropriately transfused with FFP in the presence of normal coagulation profile.…”
Section: The Ffp Transfusion Episodes Were Divided Asmentioning
confidence: 57%
“…Whereas appropriateness of FFP usage was 67 & 66.44% in recent studies conducted by Puri V et al & shah N et al respectively which is similar with our study. 26,23 Comparative analysis of FFP audits show varied indications of inappropriate use including volume expansion, bleeding with normal coagulation profile, or non-available coagulation profile leading cause of inappropriate use in our study was found to be in bleeding or non-bleeding patients with PT/INR non availability or within normal limits or mildly elevated. Luk et al found maximum patients to be inappropriately transfused with FFP in the presence of normal coagulation profile.…”
Section: The Ffp Transfusion Episodes Were Divided Asmentioning
confidence: 57%